Molecular Mechanisms Underlying Obesity-Induced Hypothalamic Inflammation and Insulin Resistance: Pivotal Role of Resistin/TLR4 Pathways - Benomar, Yacir; Taouis, Mohammed (Frontiers in Endocrinology, 2019)
Low-grade inflammation and insulin resistance are among the clinical features of obesity that are thought to promote the progressive onset of type 2 diabetes. However, the underlying mechanisms linking these disorders remain not fully understood. Recent reports pointed out hypothalamic inflammation as a major step in the onset of obesity-induced insulin resistance. In light of the increasing prevalence of obesity and T2D, two worldwide public health concerns, deciphering mechanisms implicated in hypothalamic inflammation constitutes a major challenge in the field of insulin-resistance/obesity. Several clinical and experimental studies have identified resistin as a key adipokine linking insulin-resistance to obesity, notably through the activation of Toll Like Receptor (TLR) 4 signaling pathways. In this review we present an overview of the molecular mechanisms underlying obesity-induced hypothalamic inflammation and insulin resistance with peculiar focus on the role of resistin/TLR4 signaling pathway.